The Imagery and Symbolism of Fire in the Homeric Hymns and in Greek Choral Lyric - Stuligrosz, Magdalena (Polskie Towarzystwo Filologiczne, 2020)
The paper discusses the imagery of fire in the Homeric Hymns and in selected works of the Greek lyric poets, with a particular emphasis on Pindar and Bacchylides. It demonstrates how choral lyric authors use the symbolism of fire established in the Greek epic tradition and philosophical reflection, imbuing it with new meanings and painting images which illustrate the ambiguous nature of the element of fire, based on metaphors, similes and ecphrases.
Keywords: Homeric Hymns; Pindar; Bacchylides; Greek Choral Lyric